Fertirrigação com nitrogênio e silicato de potássio na cultura de alface (Lacctuca sativa L.) em ambiente protegido - Souza, Renan Soares de (2015)
It was aimed, with the present work, to evaluate the response of lettuce, cultivar Vera, with respect to production, commercial quality, dry mass and accumulation of macronutrients (shoot), when cultivated in protected environment and conducted under fertirrigation with nitrogen and potassium silicate. Two experiments, one in the winter and spring period of the year 2012 (WS) and another in the autumn period of the year 2013 (A), were evaluated individually and, in each one of them, were used ten treatments, arranged in a completely randomized design with three replications. The composition of nine treatments occurred by the use of the Plan Puebla III matrix, which combined five N doses (9; 54; 90; 126 e 171 kg ha-1) with five potassium (potassium oxide - K2O) and silicon (Si) doses (1.15; 6.90; 11.50; 16.10 e 21.85 kg ha-1). The doses were applied in topdressing and by fertirrigation, by operation of a drip micro-irrigation system, with the use of urea, as N source, and of the commercial liquid product Fertisilício (potassium silicate based), as potassium and silicon source, but in the control, that totalized the treatments, there was not fertirrigation. The highest result for shoot commercial fresh mass, in the WS period, was observed in the major dose of Si and K2O and in the zero dose of N, however, it was found negative interaction among the doses of N, Si e K2O as from 17.00 kg Si and K2O ha-1 and 166.66 kg N ha-1. For the WS experiment, the major doses of N and of Si and K2O provided the highest shoot commercial dry mass (SCDM), and the superior responses for accumulations of magnesium (Mg), calcium (Ca), potassium (K) and phosphorus (P) in the SCDM occurred both in the major dose of N and in the major dose of Si and K2O. In the A period, only the fertirrigation with nitrogen favored the shoot commercial fresh mass, the shoot commercial dry mass and the accumulations of Mg, K, N and P in the SCDM, whose superior results were found in the major dose of N. However, in the A experiment, both the fertirrigation with nitrogen and the fertirrigation with potassium silicate influenced of positive manner the accumulations of calcium and sulfur (S) in the SCDM, with the superior responses observed both in the major dose of N and in the major dose of Si and K2O.